2021
DOI: 10.31849/reila.v3i3.7961
|View full text |Cite
|
Sign up to set email alerts
|

Vietnamese EFL Teachers’ Perceptions and Practices of Reflective Teaching as a Tool for Professional Development

Abstract: Growing professionally is considered a crucial goal that language teachers may wish to achieve in their teaching careers. Although tools for professional development can be varied in different contexts, reflective teaching as an essential and ongoing job is likely to be among the most common ones. The contributions of reflection on pursuing teacher professional development have been proved in numerous studies. However, research on the views and implementation of such a tool by EFL teachers in the Vietnamese co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In the context of language centers in Vietnam, there is an expanding corpus of research on PD activities and their influence on teacher satisfaction and teaching efficacy. Duong (2021) investigated the part played by PD in augmenting the effectiveness of teachers in English language teaching in Vietnamese universities. The aforementioned study found that PD activities, including workshops, conferences, and mentoring programs, substantially improve teacher efficacy and promote reflective teaching practices.…”
Section: Professional Development In Vietnammentioning
confidence: 99%
“…In the context of language centers in Vietnam, there is an expanding corpus of research on PD activities and their influence on teacher satisfaction and teaching efficacy. Duong (2021) investigated the part played by PD in augmenting the effectiveness of teachers in English language teaching in Vietnamese universities. The aforementioned study found that PD activities, including workshops, conferences, and mentoring programs, substantially improve teacher efficacy and promote reflective teaching practices.…”
Section: Professional Development In Vietnammentioning
confidence: 99%
“…As a result, more gratifying learning rewards will find them right after they accomplish particular teaching learning activities. Tuan (2021) pinpointed the saliency of habituating EFL educationalists to the continual reflective teaching practice by which they can inspire more emotionally-supportive learning enterprises in various classroom dominions eventually resulting in the full attainment of fruitful learning outcomes.…”
Section: Theme 1: Reflective Teaching Practice Transforms Efl Educato...mentioning
confidence: 99%
“…In that context, it is implicated that PD planners and academic managers need to avoid top-down information provision; rather, they could try to focus on using teacher-practitioner inquiry as a method of PD delivery. Teacher-practitioner inquiry is a thinking tool for teachers to flexibly customize their teaching and derive meanings, assumptions, and beliefsin-action that underlie their ideas and methodologies in class (Groundwater-Smith and Dadds, 2004;Ngo, Cherrington, and Crabbe, 2022;Phan, 2020;Pringle, 2020;Tuan, 2021). Specifically, teacher-practitioner inquiry offers a structured sense-making opportunity, such as doing a scaffolded collaborative lesson planning, inviting them to explore and justify their own pedagogical practices through lesson study and reflective practices in a trusting environment (Duffy, 1995;Gutierez, 2019;McArdle and Coutts, 2010;Robbins, 2020).…”
Section: Introductionmentioning
confidence: 99%